Spinal Cord Cells from Pre-metamorphic Stages Differentiate into Neurons and Promote Axon Growth and Regeneration after Transplantation into the Injured Spinal Cord of Non-regenerative Xenopus laevis Froglets - Méndez-Olivos, Emilio E.; Muñoz, Rosana; Larraín, Juan (Frontiers in Cellular Neuroscience, 2017)
Mammals are unable to regenerate its spinal cord after a lesion, meanwhile, anuran amphibians are capable of spinal cord regeneration only as larvae, and during metamorphosis, this capability is lost. Sox2+ cells present in the spinal cord of regenerative larvae are required for spinal cord regeneration. Here we evaluate the effect of the transplantation of spinal cord cells from regenerative larvae into the resected spinal cord of non-regenerative stages. Donor cells were able to survive up to 60 days after transplantation in the injury zone. During the first 3-weeks, transplanted cells organize in neural tube-like structures formed by Sox2+ cells. This was not observed when donor cells come from non-regenerative froglets. Mature neurons expressing NeuN and Neurofilament-H were detected in the grafted tissue 4 weeks after transplantation concomitantly with the appearance of axons derived from the donor cells growing into the host spinal cord, suggesting that Sox2+ cells behave as neural stem progenitor cells. We also found that cells from regenerative animals provide a permissive environment that promotes growth and regeneration of axons coming from the host. These results suggest that Sox2 cells present in the spinal cord of R-stage larvae are most probably neural stem progenitor cells that are able to survive, proliferate, self-organize and differentiate into neurons in the environment of the non-regenerative host. In addition, we have established an experimental paradigm to study the biology of neural stem progenitor cells in spinal cord regeneration.